Waiting Time for Coronal Preparation and the Influence of Different Cements on Tensile Strength of Metal Posts - Ilione Kruschewsky Costa Sousa Oliveira; Ynara Bosco de Oliveira Lima Arsati; Roberta Tarkany Basting; Fabiana Mantovani Gomes França (International Journal of Dentistry)
This study aimed to assess the effect of post-cementation waiting time for core preparation of cemented cast posts and cores had on retention in the root canal, using two different luting materials. Sixty extracted human canines were sectioned 16 mm from the root apex. After cast nickel-chromium metal posts and cores were fabricated and luted with zinc phosphate (ZP) cement or resin cement (RC), the specimens were divided into 3 groups (n = 10) according to the waiting time for core preparation: no preparation (control), 15 minutes, or 1 week after the core cementation. At the appropriate time, the specimens were subjected to a tensile load test (0.5 mm/min) until failure. Two-way ANOVA (time versus cement) and the Tukey tests (P < 0.05) showed significantly higher (P < 0.05) tensile strength values for the ZP cement groups than for the RC groups. Core preparation and post-cementation waiting time for core recontouring did not influence the retention strength. ZP was the best material for intraradicular metal post cementation.